Abundance : the future is better than you think - Diamandis, Peter H., ....-; Kotler, Steven, 1967- (New York : Free Press, 2014)
The authors document how four forces--exponential technologies, the DIY innovator, the Technophilanthropist, and the Rising Billion--are conspiring to solve our biggest problems. "Abundance" establishes hard targets for change and lays out a strategic roadmap for governments, industry and entrepreneurs, giving us plenty of reason for optimism.
First published: 2012.
Includes bibliographical references and index.
Keywords: Technological innovations -- Forecasting; Technological forecasting; Technology -- Social aspects; Social prediction; Economic forecasting